The 13th submission of manpower and machinery & equipment of BRACU project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of status and quantities of manpower and machinery & equipment of BRACU new campus project.